Tungsten Oxychloride Compounds Containing [W6O6Cl12]n–(n = 2, 3) Clusters. Issue 14 (9th September 2013) - Hummel, Thorsten; Glaser, Jochen; Ströbele, Markus; Meyer, H.‐Jürgen
Abstract Three tungsten oxychloride clusters containing the nearly D3d symmetric [(W6O6iCl6i)Cl6a]n– (n = 2, 3) core were prepared from the cluster acid (H5O2)2[W6O6Cl12]·4H2O and structurally characterized by single‐crystal X‐ray diffraction. The copper compound [Cu(H2O)4][W6O6Cl12]·12H2O releases water molecules to yield [Cu(H2O)6][W6O6Cl12]. Both compounds are represented as diamagnetic clusters, having 14 electrons in W–W bonding states. Magnetic measurements on the calcium compound [Ca(H2O)7]2[W6O6Cl12]Cl revealed a paramagnetic cluster having 15 valence electrons.